ESTIMASI KINERJA RUAS JALAN DENGAN PENGATURAN LALU LINTAS SATU ARAH PADA KAWASAN JETIS, YOGYAKARTA - prima romadhona (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2018)
One-way traffic management can be used as a solution in handling traffic problems in order to improve traffic performance. One location with traffic problems is Jetis area which has several roads with trade and commerce activities in the city of Yogyakarta. Therefore, traffic congestion and side barriers disrupt the flow of traffic on the road in Jetis Area. The purpose of this study was to estimate the performance of roads in Jetis Area if one-way traffic management is applied hence the impact. The data were obtained from the Yogyakarta Transportation Agency 2014 then analyzed and modeled with VISSIM software. As the results, before the one-way management implementation, the road with the highest v/c ratio occurred at Jalan Magelang (0.85) and the worst speed of vehicle occurred at Jalan Mangkubumi Selatan as much as 10.43 km/hour. However, with the implementation of one-way traffic management from South to North, V/C ratio increased 8% on Jalan Magelang and Mangkubumi, though 2 other segments decreased 8%. In addition, vehicle speed increased 9% in almost all roads except Jalan Wolter Mangunsidi decreased 2%.